Assessment of the nervous system state in low birth weight children taking into account the FADS2 rs174583 (C/T) gene polymorphism - Shumna T. Yе.; Levchuk-Vorontsova, T. O. (Zaporozhye Medical Journal, 2020)
Aim. To assess the neurological status and index of neuropsychological development in low birth weight children taking into account the FADS2 rs174583 (C/T) gene polymorphism. Materials and methods. To study the FADS2 rs174583 (C/T) gene polymorphism, 170 children were examined. The children were divided into 3 groups depending on their birth weight: group I included 53 children (birth weight was 1500–1999 g, gestation period – 33.0 [32.0; 35.0] weeks), group II included 77 children (birth weight – 2000–2499 g, gestation period – 35.0 [34.0; 36.0] weeks), group III was composed of 40 children as a control (birth weight – more than 2500 g, gestation period – 38.0 [36.0; 39.0] weeks). The genotyping was carried out using a polymerase chain reaction method. Results. The C allele and the С/Т genotype frequencies of the FADS2 rs174583 gene polymorphism in the children matched those in North-Western Europe. Seizures in the past medical history due to the nervous system disorders were most commonly occurred in children with the TT genotype (16.45 %, P < 0.05), while patients with the CC genotype had seizures in only 5.6 % of cases. Children with a birth weight of 1500–1999 g carrying the C/T heterozygous genotype and the T/T homozygous genotype of the FADS2 (rs1745683) gene polymorphism had a lower total Apgar score than children with a birth weight of more than 2000 g (P < 0.05). The coefficient of psychomotor development was the lowest in children with birth weight of 1500-1999 g and the minor homozygous T/T genotype of the FADS2 (rs1745683) gene polymorphism, at 83.0 (75.0; 83.0), which corresponded to a weak normal level of the neuropsychiatric development, while the highest index of psychomotor development (116.0 (112.0; 141.0)) and a normal high level of neuropsychiatric development were significantly registered in children with birth weight of 2500 g and the major homozygous C/C genotype. Conclusions. It is possible that the predominance of the homozygous C/C genotype and the heterozygous C/T genotype fulfils a protective function in order to reduce the negative effects of preterm birth on the nervous system.